2014
DOI: 10.1007/s10853-014-8419-5
|View full text |Cite
|
Sign up to set email alerts
|

Hardness and flexural strength of single-walled carbon nanotube/alumina composites

Abstract: This work adds new experimental facts on room temperature hardness and flexural strength of alumina and composites with 1, 2, 5 and 10 vol.% single walled carbon nanotubes (SWNT) with similar grain size. Monolithic Al 2 O 3 and composites were spark plasma sintered (SPS) in identical conditions at 1300ºC, achieving high density, submicrometric grain size and a reasonably homogeneous distribution of SWNTs along grain boundaries for all compositions with residual agglomerates. Vickers hardness values comparable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“…The results of flexural strength of composite C4 of this study, s F ¼ 600 ± 50 MPa, are analogous to the flexural strength for 1 vol% SWNT/Al 2 O 3 (in the range 520e610 MPa) [33] (composite tested with the same experimental set up and same specimen dimensions). They are also comparable to the value s F ¼ 526 ± 84 obtained for 1.2 vol% DWNT/ 3YTZP [42].…”
Section: Mechanical Propertiessupporting
confidence: 65%
See 3 more Smart Citations
“…The results of flexural strength of composite C4 of this study, s F ¼ 600 ± 50 MPa, are analogous to the flexural strength for 1 vol% SWNT/Al 2 O 3 (in the range 520e610 MPa) [33] (composite tested with the same experimental set up and same specimen dimensions). They are also comparable to the value s F ¼ 526 ± 84 obtained for 1.2 vol% DWNT/ 3YTZP [42].…”
Section: Mechanical Propertiessupporting
confidence: 65%
“…This result can be explained with the same arguments used to analyze flexural strength results from Al 2 O 3 / SWNT composites [33]. In these alumina composites, with SWNT content ranging from 1 to 3 vol%, flexural strength decreased when SWNT increased.…”
Section: Mechanical Propertiesmentioning
confidence: 66%
See 2 more Smart Citations
“…To the best of our knowledge, absence of decrease or increase of hardness with increasing CNT content in ceramic matrix composites has only been reported for Al 2 O 3 with 1 vol% SWNT composites, 34 since most of the authors report a decrease of hardness, even for composites with low CNT content. 11, [14][15][16] The decreasing trend reported by previous authors for 3YTZP/CNT composites is shown in Figure 4(a).…”
Section: Mechanical Propertiesmentioning
confidence: 84%